Цензурна історія "Чорної ради" П. Куліша. Вступ до проблеми - Федорук, О.О. (Слово і Час, 2019)
У статті пунктирно окреслено проблему взаємин Куліша з царською цензурою під оглядом вужчої проблематики – цензурної історії української та російської версій роману “Чорна рада”. Умовно виокремлено кілька періодів: до Кулішевого арешту у справі Кирило-Мефодіївського братства, заслання в Тулі, відразу по звільненню із заслання, після зняття цензурного обмеження у квітні 1856 р. A censor history is one of the most important issues in the textual study of Kulish’s novel “The Black Council”. However, this problem has never been considered before by the Ukrainian scholars, and even more general issue, i.e. “Kulish and the Censorship”, was not involved much into the field of research. This paper gives an introduction to this topic shedding some light on the censor history of “The Black Council”. Relations between Kulish and the tsarist censorship in different times were ambiguous which was caused by several reasons. The first one was individual approach of the censors to his works which might be connected, in particular, with the trial of Saints Cyril and Methodius Brotherhood (1847). Other reason was general persecution of the Ukrainian literature, especially after the Ems Ukase (1876). In order to circumvent censorship Kulish published his works also abroad. Before Kulish was arrested he wrote his works without paying particular attention to the censorship. The first writer’s concerns about possible restrictions that might be imposed on his works by the censorship arose with the novel “The Black Council”. Kulish’s arrest radically changed circumstances of his life and creative activity. Until 1856 he had to submit his works to prior censorship consideration and used pseudonym Nikolai M. (the name of his friend Nikolai Makarov) to avoid these restrictions. The Third Department of His Imperial Majesty’s Personal Chancellery allowed Kulish to publish his works on the base of the general censor regulations only in April 1856. In a short time Kulish sent the manuscript of “The Black Council” to the censorship committee.